Synthesis of nanosilica form sugarcane bagasse using the sol-gel method for enhanced nano fluid applications / Kagren John Kumar ... [et al.] - Kumar, Kagren John; Subari, Fuzieah Subari; Abdullah, Zalizawati; Kasmuri, Nor Hazelah; Kamaruddin, Nadia (Penerbit UiTM (UiTM Press), 2025)
Nanomaterials have gained immense popularity in advanced materials research due to their unique properties and potential applications in various fields. This study synthesizes nanofluids from ash-derived sugarcane bagasse nanosilica and evaluates their potential for practical and industrial applications. Using a sol-gel method and a two-step ultrasonication process, the nanofluids were characterized for particle size, agglomeration, stability, and viscosity. SEM images revealed irregularly shaped nanosilica particles with rough surfaces, indicating high surface areas and a tendency to agglomerate.